Constitution and application of RPC constitutive model - Kejia, Yang; Wei, Li; Lianmeng, Chen; Ziling, Xie (Journal of Structural Engineering, 2025)
The damage evolution equation of Reactive Powder Concrete (RPC) is established based on 2-parameter Weibull distribution. The constitutive relation of RPC is then calculated based on the damage evolution equation and definition of damage index. Considering that there are no damage in the elastic stage, a threshold strain is inserted in the constitutive model. The constitutive models corresponding to 4 threshold strains are calculated, and the constitutive model of RPC is optimized by comparing experimental constitutive curve to models corresponding to different threshold strain. Based on the definition of damage index in ABAQUS, the damaged evolution equation in ABAQUS is recalculated based on the optimized constitutive model. The parameters of concrete damaged plasticity model in ABAQUS are then calculated by using the aforementioned procedure. And the RPC concrete damaged plasticity model can be built in ABAQUS. The RPC damaged plasticity model is applied to three compression members and three simply supported beams with different reinforcements. The calculated stress-strain curve and deformation of three compression member and three beams is in accordance with the deformation characteristics of experiments, which verified the effectiveness of the proposed concrete damaged plasticity model of RPC.